UPAYA MEMBANGUN NILAI RELIGIUS PESERTA DIDIK MELALUI KEGIATAN PONDOK RAMADHAN DI SMP NEGERI 17 MALANG - Awanda Eka Pratiwi; Muhammad Zainul Muttaqin; Krisna Andi Olyffia; Ainun Nisak Ul Qoriah; Yuni Setyowati; Yurika Brilyan Astriana; Najib Jauhari; Awanda Eka Pratiwi; Muhammad Zainul Muttaqin; Krisna Andi Olyffia; Ainun Nisak Ul Qoriah; Yuni Setyowati; Yurika Brilyan Astriana (Universitas Negeri Malang, 2024)
The role of religion and technology in society, highlighting how technology facilitates access to religious knowledge and can also be misused, causing social problems such as radicalization and teenage pregnancy. This emphasizes the importance of guiding teenagers through their development, including religious education and preventive measures such as communal religious approaches. Finally, specific initiatives were mentioned, such as the Pondok Ramadhan program at SMPN 17 Malang, which aims to strengthen religious values among students. This research adopts a qualitative approach because it aims to reveal phenomena that occur in the field, which are then explained in written form rather than numerical data. Qualitative research is a research method that produces descriptive data in the form of written or spoken words from people and observable behavior. Research shows that Pondok Ramadhan activities at SMP Negeri 17 Malang have succeeded in developing religious character and increasing the spiritual values of students in a programmatic manner. Students demonstrated full participation in these activities, with positive changes in habits such as increased awareness of prayer times and participation in congregational worship. Schools play a role in forming students' awareness and independence in applying religious values, both in the context of worship and daily behavior, as well as strengthening social values such as generosity and giving alms.